The effect of regulatory focus on customer citizenship behavior in a virtual brand community: The role of online self‐presentation and community identification. Issue 3 (19th October 2020) - Wang, Li; Sakashita, Mototaka; Cheng, Guoping; Ji, Junzhe; Zhang, Yating
Abstract: Customer citizenship behavior (CCB) in virtual brand communities is a topic of increasing importance in marketing management research. This type of behavior plays a critical role in the improvement of enterprises' marketing capabilities. In this study, we draw on regulatory focus theory—along with the perspectives of self‐presentation and regulatory fit in relation to social identity—to construct and test a model that investigates both the main effects of regulatory foci (promotion and prevention) and the indirect effects of online self‐presentation and community identification on CCB. The empirical results based on our online survey between 310 individual members of an well‐known online‐community in China demonstrate: (1) a promotion focus exerts a positive influence on CCB while a prevention focus exerts a negative impact; (2) the desire for online self‐presentation mediates the association between regulatory foci and CCB; and (3) community identification moderates the relationship between regulatory foci and the desire for online self‐presentation, as well as the mediation effect. These results have substantial implications for studying CCB within virtual brand communities.